Secure IT systems : 23rd Nordic Conference, NordSec 2018, Oslo, Norway, November 28-30, 2018, Proceedings /: 23rd Nordic Conference, NordSec 2018, Oslo, Norway, November 28-30, 2018, Proceedings. (2018) - Unknown
No abstract available